Humidity, temperature and air velocity data logger for thermal comfort application - Rashila Baharudin
This project is to create a thermal comfort system in different environment such as seated relaxed, clock repairer, laboratory and others. It measures the temperature and humidity using respective sensor that connected to a Data Logger and Lab VIEW.